PENGARLTH PUPUK MIKRO PACLOBTIIAZOL DAN KNO3 TERHADAP TANAMAN MELATI EMPRITn(JAMINUN SAMBAC L) - Hayati Soeprapto (LPPM Universitas Pekalongan, 2007)
This research was join betv'een agricultural Academi oJMuhammadiyah (AMP.) Penalang and the Branch of Teclmolog)Aplication and Stltdy (BPPT) Serpong, Tangerung. The aims oJlesearch were: (1) sludying the inluence offertilizing degee ofmacfo KNO s toutord the grcteth and prcduclion of Melati E prit(Jasminum sambac), (2) studying the influence offeltilizingdegree of micro Paclobotazol (PCB), towotd the growth theproduction of Melali Emprit (Jasminnh sambac), (3) studyingthe posibilily of interaclional infuence befleeen Jertilizer oJ macroKNO r and micro PCB, and (4) fnding the optimnn dose of macroKNO3 fertilizer and micro Paclobutazol fertilizet tolrotd thegroith and ptoduction of Mebti Emprit (Jasminum sambac) ina jasmine prod ction centerThe res t after research showed the fetilizer of macro KNO.had no infuence toword the growlh and productio of MelatiEmprit (Jasminum sambac). The application og fertilizer of nicroPaclobutazol (PCB) had also no Wuence toword the grc\9tha d production of Melati Emprit (Jasminum sambac). Mea vhile,there was also no inleraclional influence between fertilizel ofmacro KNO| and fertilizer of micro Prclobutazol (PCB) towordthe gowth and production of Melati Empril (Jasminum sambac).Finally, there was no fnding about the optimum dose oflefiilizerof macro KNO3and fe ilizer ofmicro Paclobttazol (PCB) towordthe grol)th and podrctiorl of Melati Emplil (Jasmin&n sambac)Keywords: pengatxh, paclob razol, kno3, melati emptit(iamimtn sambac l.)